Pengaruh Penggunaan E-Commerce dan Promosi Online terhadap Perilaku Belanja Mahasiswa Fakultas Ekonomi Universitas Mahaputra Muhammad Yamin - Syarifah Mutia; Dwi Anissa Rahmanillahi; Meyriska Eka Putri; Karin Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of e-commerce has transformed consumer shopping behavior, particularly among university students, who constitute an active group of internet users. In addition to the convenience offered by e-commerce, online promotions have also become one of the factors that may influence students’ shopping behavior. This study aims to determine the effects of e-commerce usage and online promotions on university students’ shopping behavior. This study employed a quantitative method with an associative approach. The population consisted of 145 students, with a sample of 107 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using SPSS Version 25. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results showed that e-commerce usage had a positive and significant effect on students’ shopping behavior, with a calculated t-value of 2.728, which was greater than the critical t-value of 1.659, and a significance value of 0.007, which was less than 0.05. Online promotions also had a positive and significant effect on students’ shopping behavior, with a calculated t-value of 4.609, which was greater than the critical t-value of 1.659, and a significance value of 0.000, which was less than 0.05. Simultaneously, e-commerce usage and online promotions had a significant effect on students’ shopping behavior, with a calculated F-value of 45.155, which was greater than the critical F-value of 3.08. The most dominant variable influencing students’ shopping behavior was online promotion.